Data information literacy instruction in Business and Public Health: Comparative case studies. (December 2016) - Macy, Katharine V.; Coates, Heather L.
Employers need a workforce capable of using data to create actionable information. This requires students to develop data information literacy competencies that enable them to navigate and create meaning in an increasingly complex information world. This article examines why data information literacy should be integrated into program curricula, specifically in the instances of business and public health, and offers strategies for how it can be accomplished. We approach this as a comparative case study within undergraduate business and master of public health programs at Indiana University-Purdue University Indianapolis. These case studies reveal several implications for practice that apply across social and health sciences programs.